Hubungan Antara Derajat Depresi Dan Kecemasan Dengan Beban Pengasuh Penderita Kanker Yang Mendapatkan Kemoterapi - Titis Hadiati; Natalia Kus Setiarini; Hang Gunawan Asikin (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Introduction: Cancer causes a significant physical and emotional burden, not only for patients, but also for caregivers. Caregiver’s burden is associated with caring for a chronically ill family member, which would increase if role tensions and concerns related to cancer are high and/or if they are in poor physical and emotional health, such as depression or anxiety. This study aims to determine the relationship between depression and anxiety with the burden of caregivers of cancer patients receiving chemotherapy.Method: A cross-sectional study with consecutive sampling involving caregiver of cancer patients who met the inclusion and exclusion criteria. The sample filled out the DASS-21 and ZBI questionnaires to determine the degree of depression, anxiety, and caregiving burden. The relationship between variables was obtained using the Spearman test.Results: From 30 caregivers of cancer patients who received chemotherapy, 3 experienced mild depression, 1 experienced moderate depression, 7 experienced severe depression, and 2 experienced very severe depression. While 5 experienced mild anxiety, 3 experienced moderate anxiety, 4 experienced severe anxiety, and 5 experienced very severe anxiety. ZBI showed 18 with little or no burden, 3 with mild to moderate burden, 4 with moderate to severe burden, and 5 with severe burden. There is a significant correlation between the degree of depression and anxiety with the burden of caring for cancer patients who receive chemotherapy (p less than 0,001).Conclusion: Depression and anxiety are associated with the burden of caring for cancer patients who receive chemotherapy due to the tension and worry related to cancer with various symptoms and chemotherapy side effects.